MENINGKATKAN NIAT BERKUNJUNG PADA GENERASI MUDA MELALUI CITRA DESTINASI DAN DAYA TARIK KAMPUNG WISATA - Cahyanti, Mega Mirasa; Anjaningrum, Widiya Dewi (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2017)
This study aims to determine the effects of destination image and tourism attractiveness variables on intention of young generation to visit a rural tourism destination such as “Kampung Wisata Tridi”. This research is a kind of causal research, where the primary quantitative data through questionnaire was taken directly from a tourists in tourism destination and also them who included as young generation. To fulfill the criteria of sample that needed on this research, the sampling technique was used is purposive sampling, by the consideration that sampling choosen is vary between 17-33 years old, and willing to fill the questionnaire. Based on the target that researcher have, a predetermine number of samples that taken was 50 respondents. Based on the result taken by data processing using SPSS 23, shows that the variable which effect significantly the intention to visit a tourism destination are destination image and tourism attractiveness. In other hand, variable which effect most significantly was tourism attractiveness compare with destination image.